Ambient concentrations and deposition rates of selected reactive nitrogen species and their contribution to PM2.5 aerosols at three locations with contrasting land use in southwest China. (February 2018) - Song, Ling; Liu, Xuejun; Skiba, Ute; Zhu, Bo; Zhang, Xifeng; Liu, Meiyu; Twigg, Marsailidh; Shen, Jianlin; Dore, Anthony; Reis, Stefan; Coyle, Mhairi; Zhang, Wen; et al.
Abstract: The fast economic development of southwest China has resulted in significant increases in the concentrations of reactive nitrogen (Nr) in the atmosphere. In this study, an urban (Chengdu, CD), suburban (Shifang, SF) and agriculture (Yanting, YT) – dominated location in the Sichuan Province, southwest China, were selected to investigate the atmospheric composition of Nr, their concentrations and deposition rates. We measured Nr concentrations in precipitation (NH4 +, NO3 − and organic N (DON)), the gas phase (NH3 and NO2 ), and the aerosol particles (PM2.5 ), and calculated their fluxes over a two year period (2014–2016). Total annual N deposition rates were 49.2, 44.7 and 19.8 kg N ha −1 yr −1 at CD, SF and YT, respectively. Ammonia concentrations were larger at the urban and suburban sites than the agricultural site (12.2, 14.9, and 4.9 μg N m −3 at CD, SF and YT, respectively). This is consistent with the multitude of larger sources of NH3, including city garbage, livestock and traffic, in the urban and suburban areas. Monthly NO2 concentrations were lower in warmer compared to the colder months, but seasonal differences were insignificant. Daily PM2.5 concentrations ranged from 7.7 to 236.0, 5.0–210.4 and 4.2–128.4 μg m −3 at CD, SF and YT, respectively, and showed significant correlations with fine particulate NH4 + and NO3 − concentrations. Ratios of reduced to oxidized N were in the range of 1.6–2.7. This implies that the control of reduced Nr especially in urban environments is needed to improve local air quality. Highlights: NH3 concentrations were high in both urban and suburban regions. 75–97% of monitored 24-h PM2.5 concentrations exceeded the WHO standard. Reactive nitrogen concentrations correlated significantly with PM2.5 concentrations. Reduced nitrogen dominated in both bulk and dry nitrogen deposition. Abstract : Reduced nitrogen compounds dominate bulk and dry nitrogen deposition in southwest China and contribute considerably to PM2.5 aerosol formation.